Polymer chalcogenides—new smart materials for thermoelectric applications. (1st July 2022) - Maity, Shilpa; Parvin, Umme Karnij Salma; Das, Sukhen; Chatterjee, Krishanu
Abstract: The breakthrough invention of conducting polymers (CPs) initiates a new pathway for the researchers to make use of their properties in thermoelectric (TE) applications. They are considered to be potential candidates in TE application when combined with inorganic counterparts. Different strategies were undertaken to enhance structural order and hence the TE performance of the CPs which trigger the scientific community to focus more on this area. Consequently, the use of nano filler in the polymer matrix proved to be a better way to improve the TE properties and chalcogenide materials could be the best candidates to be used as nano filler due to their high TE parameters. Thus, composites of CPs with different chalcogenides have been drawing attention in the field of TEs in recent years. The present work points towards a comprehensive update on different synthesis process of composites of various CPs with a number of chalcogenides along with a state-of-art review of these promising materials in TEs for device applications with the expectation that this work will surely motivate the researchers to optimize the best candidate.